The Structure of the Money-Expenditures Relationship: Reply - Peltzman, Sam (American Economic Review, 1970)
Dwight Jaffee's most important criticism of my article is that the empirical estimates of the model gratuitously excluded a variable, and that this biased downward my estimate of the long-run interest elasticity of velocity. Since the most notable difference between my article and the bulk of the literature on the demand for money is my finding of an essentially zero interest-elasticity of velocity, Jaffee's criticism is surely germane. However, Jaffee has misinterpreted mv model, and, even if his misinterpretation is accepted, his empirical results do little violence to the findings. Jaffee's misinterpretation of my model can be seen by comparing his equation (2) with equation (1) in my article, which I rewrite, adopting Jaffee's notation: